Transforming Diversity into Inclusion: A Multicultural Education Framework for United States Higher Education - Osman Öztaşkan (Journal of Cultural Relativism (JCR), 2026)
Higher education institutions in the United States are experiencing increasing cultural, ethnic, linguistic, and socioeconomic diversity as a result of globalization, migration, and expanding educational access. While diversity has become a defining characteristic of American higher education, transforming diversity into meaningful inclusion remains a significant challenge. This study examines the role of multicultural education in fostering inclusive learning environments and promoting equitable participation within United States higher education institutions. Using a systematic literature review approach, the study synthesizes contemporary research on multicultural education, diversity, inclusion, intercultural competence, and higher education equity. The findings indicate that multicultural education contributes to inclusive campus cultures by promoting cultural awareness, reducing discrimination, strengthening intercultural competence, and supporting student engagement across diverse populations. Furthermore, the study proposes a conceptual framework that explains how multicultural educational practices facilitate the transition from demographic diversity to institutional inclusion through the mediating processes of intercultural engagement and inclusive participation. The findings provide theoretical and practical insights for policymakers, educational leaders, and faculty members seeking to develop inclusive and socially responsive higher education environments.